2019
DOI: 10.1242/jcs.228213
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Hsp90α and clusterin synergistically promote breast cancer epithelial-to-mesenchymal transition and metastasis via LRP1

Abstract: Extracellular heat shock protein 90 alpha (eHsp90α, also known as HSP90AA1) has been widely reported to promote tumor cell motility and tumor metastasis in various types of cancer. Several extracellular proteins and membrane receptors have been identified as interacting proteins of eHsp90α and mediate its pro-metastasis function. However, the regulatory mechanism of eHsp90α activity remains largely unknown. Here, we report that clusterin, a protein newly demonstrated to interact with eHsp90α, modulates eHsp90α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 65 publications
3
58
0
Order By: Relevance
“…Festuccia et al also reported that CEP-701, a pan TRK inhibitor, could effectively reduce metastasis in advanced prostate cancer 50 . Recently, Tian et al explained that LRP2 played an important role in tumor cell motility and the tumor metastasis mechanism regulated by Hsp90α 51 . All these studies support our conclusion from this study that NTRK3 and LRP2 might be prognosis biomarkers for Chinese ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Festuccia et al also reported that CEP-701, a pan TRK inhibitor, could effectively reduce metastasis in advanced prostate cancer 50 . Recently, Tian et al explained that LRP2 played an important role in tumor cell motility and the tumor metastasis mechanism regulated by Hsp90α 51 . All these studies support our conclusion from this study that NTRK3 and LRP2 might be prognosis biomarkers for Chinese ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…CLU is involved in basic BPs, such as cell death, neurodegenerative disorder, and tumor progression (Bertacchini et al, 2019;Seo et al, 2019). Previous studies also demonstrated that the CLU protein can interact with HSP90AA1 and enhance the effect of HSP90AA1 on the activation of the Eph receptor B1 (ERK), AKT serine/threonine kinase 1 (AKT), and nuclear factor kappa B (NF-κB) families, in addition to epithelial-tomesenchymal transition and migration in breast cancer cells (Tian et al, 2019). The CLU protein is mainly produced by rat Sertoli cells and protects surviving cells during heat stress by binding to toxic compounds or dissolving cellular debris released by the degenerating cells (Clark and Griswold, 1997).…”
Section: Cross-species Analysis Of Candidate Genesmentioning
confidence: 99%
“…Its overall function remains nevertheless extremely complex to decipher especially because the deregulation degree of its expression is highly variable depending on the type of tumors and the stage of cancer progression. In malignant diseases, the current trend seems to correlate LRP-1 overexpression with poor prognostic, increased cell proliferation, invasiveness and tumor recurrence (Catasus et al, 2011;Gheysarzadeh et al, 2019;Tian et al, 2019). To date, few studies have examined the contribution of LRP-1 in the field of CRC despite obvious clinical interest.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tumor growth and metastasis, the molecular contribution of LRP-1 remains misunderstood and be highly dependent of the tumor microenvironment. Although LRP-1 expression and its role in cancer hallmarks are now well referenced in glioma (Boyé et al, 2017), melanoma (Salama et al, 2019), thyroid (Perrot et al, 2012;Appert-Collin et al, 2017;Theret et al, 2017), and breast carcinoma (Beaujouin et al, 2010;Tian et al, 2019), little is known about LRP-1 functionalities in colorectal carcinoma (CRC). LRP-1B, a member of LDL-R family highly homologous to LRP-1, is downregulated in the colon cancer tissues and inhibits the growth, migration and metastasis of colon cancer cells (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%